Cis-acting modifiers in the ABCA4 locus contribute to the penetrance of the major disease-causing variant in Stargardt disease. Issue 14 (28th April 2021) - Lee, Winston; Zernant, Jana; Nagasaki, Takayuki; Molday, Laurie L; Su, Pei-Yin; Fishman, Gerald A; Tsang, Stephen H; Molday, Robert S; Allikmets, Rando
Abstract: Over 1200 variants in the ABCA4 gene cause a wide variety of retinal disease phenotypes, the best known of which is autosomal recessive Stargardt disease (STGD1). Disease-causing variation encompasses all mutation categories, from large copy number variants to very mild, hypomorphic missense variants. The most prevalent disease-causing ABCA4 variant, present in 20% of cases of European descent, c.5882G > A p.(Gly1961Glu), has been a subject of controversy since its minor allele frequency (MAF) is as high as 0.1 in certain populations, questioning its pathogenicity, especially in homozygous individuals. We sequenced the entire 140Kb ABCA4 genomic locus in an extensive cohort of 644 bi-allelic, i.e. genetically confirmed, patients with ABCA4 disease and analyzed all variants in 140 compound heterozygous and 10 homozygous cases for the p.(Gly1961Glu) variant. A total of 23 patients in this cohort additionally harbored the deep intronic c.769-784C > T variant on the p.(Gly1961Glu) allele, which appears on a specific haplotype in 15% of p.(Gly1961Glu) alleles. This haplotype was present in 5/7 of homozygous cases, where the p.(Gly1961Glu) was the only known pathogenic variant. Three cases had an exonic variant on the same allele with the p.(Gly1961Glu). Patients with the c.[769-784C > T;5882G > A] complex allele exhibit a more severe clinical phenotype, as seen in compound heterozygotes with some more frequent ABCA4 mutations, e.g. p.(Pro1380Leu). Our findings indicate that the c.769-784C > T variant is major cis -acting modifier of the p.(Gly1961Glu) allele. The absence of such additional allelic variation on most p.(Gly1961Glu) alleles largely explains the observed paucity of affected homozygotes in the population.